The experience of children using long-term non-invasive ventilation: a qualitative study - Olmstead, Deborah; Carroll, Allison; Klein, Jennifer; MacLean, Joanna E. (Frontiers in Sleep, 2024)
Objectives To identify factors to optimize long-term non-invasive ventilation (LT-NIV) use by exploring the experience of children using LT-NIV and their parents. Study design and methods A qualitative framework analysis method was used. Children aged 8–12 years who used LT-NIV for at least 3-months and their parents/guardians were approached to participate. Thematic analysis of data derived from focus group interviews, conducted separately for children and parents, was performed. Findings were coded and grouped into identified themes. Results Data analysis identified four themes: (1) “The double-edged sword,” which identified benefits and challenges of LT-NIV use; (2) “Feeling different,” where children and parents described fears, frustrations, and concerns including emotional and social implications, and physical changes; (3) “It's not just about the mask,” highlighted the influence of equipment issues, including the mask interface, headgear, tubing and humidity, and their impact on tolerance and use of LT-NIV; and (4) “Through the eyes of experience—children and parents as experts for change,” which captured ideas for the functional and aesthetic improvement of the equipment including the need for pediatric specific technology. Conclusions LT-NIV use has two sides; it helps to improve lives though requires an investment of time and commitment to ensure success. Investing in pediatric-specific equipment needs to be a priority as do alliances between healthcare providers, children who use LT-NIV, and their families. Future technology development and studies of adherence need to consider the experiences of children and their families to reduce the challenges and support optimal use of LT-NIV.